DEVELOPING TEACHING MATERIALS OF ORAL LANGUAGE SKILLS KKNI BASED OF ENGLISH EDUCATION STUDY PROGRAM UNIMED - Nora Ronita Dewi (BAHAS, 2017)
This study is aimed at developing teaching materials of oral language skill KKNI based of English Education Study Program at UniversitasNegeri Medan. The objectives of this research are to analyze the teaching materials of Oral Language Skills used at the 2nd semester of English Education Study Program and develop the appropriate teaching materials based on the students’ needs. Research and Development applied in this research and skills covered in oral language both listening and speaking. The results show that the teaching materials used in the 2nd semester at English Education Study Program is developed through implementing the simplification of R&D. The materials indicated low competency for the students after analyzing the questionnaires given. New topics are designed to answer the needs of the students. Generally, the existing English speaking materials are less relevant with the needs of 2nd semester students. In terms of topics, they are not suitable with the needs of the Lesson Plan which make the students are less motivated in learning English. The speaking materials needed by the students are relevant with their needs where the topics or contents used in the course book are relevant and useful in the learning outcome of this subject. The topics needed are: work pressure; juggling school, work, and family; taking care of environment; change and consequences, the importance of the past, machines, cycles, and processes, arts and sciences, nature, health, and individual and society.